The nature of witches - Griffin, Rachel., 1985- (Sourcebooks Fire, 2021)
"Witches, who for centuries have maintained the climate, are losing their power as the atmosphere becomes more erratic, and all hope for a better future lies with Clara Densmore, an Everwitch whose rare magic is tied to every season"--OCLC.